2017
DOI: 10.1142/s0217979217440593
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of BiVO4/Bi2MoO6 composites with enhanced photocatalytic activity

Abstract: BiVO4/Bi2MoO6 composites have been fabricated via the one-step hydrothermal method. The properties of composites were tailored by altering the V/Mo molar ratios. Photocatalytic activities were evaluated by measuring degradation of RhB under visible-light irradiation. BiVO4/Bi2MoO6 composites with V/Mo molar ratio of 8:1 possessing the optimal photocatalytic performance. The enhanced photocatalytic activity was attributed to the efficient charge carrier separation of composite heterostructures. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The two peaks of S 2p at 158.3 and 163.6 eV were both assigned to S 2p 3/2 with spin-orbit splitting difference of 5.3 eV, these showed the S-doped in the photocatalytic were in the form of S 2− . The two peaks of S 2p coincided with the spin-orbit bimodal of Bi 4f, indicated that S 2− were successfully doped in the lattice of Bi 2 MoO 6 [34].…”
Section: Resultsmentioning
confidence: 99%
“…The two peaks of S 2p at 158.3 and 163.6 eV were both assigned to S 2p 3/2 with spin-orbit splitting difference of 5.3 eV, these showed the S-doped in the photocatalytic were in the form of S 2− . The two peaks of S 2p coincided with the spin-orbit bimodal of Bi 4f, indicated that S 2− were successfully doped in the lattice of Bi 2 MoO 6 [34].…”
Section: Resultsmentioning
confidence: 99%
“…The pH of the MB solution could affect the adsorption of the catalyst, and a good adsorption effect will also help enhance the photocatalytic degradation performance. 31 Specifically, ZnO is easy to adsorb the electrically positive MB onto the surface by electrostatic action in alkaline conditions. In addition, it is beneficial for the h + to migrate to the surface of ZnO and react with electron receptors such as H 2 O and OH − so as to produce .OH with strong catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…BET-specific surface area (S BET ) is used to characterize the adsorption capacity of the membranes, which is very important for its photocatalytic process. 31 It can be observed that the BET-specific surface area of spunlaced viscose fiber decreased from 11.421 to 9.145 m 2 /g after the modification of PANI, the reason for this phenomenon is that the diameter of SV@PANI membrane is increased. Subsequently, the ZnO nanoparticles further reduced the BET-specific surface area of SV@PANI membrane from 9.145 to 7.281 m 2 /g.…”
Section: Bet Analysismentioning
confidence: 95%